TEATRALIDADE(S) DE MAMA SOLOTKA, A CARTOMANTE DA FESTA-RITUAL DE IVANA KUPALA - STELMATCHUK, TÉSSIO LEANDRO (2023)
This dissertation aims to analyze theatricality in the interactions between spectators and the character Mama Solotka, the fortune teller of the Ukrainian ritual-festival Ivana Kupala - a midsummer festival exclusive to the city of Mallet, in the Southern region of Paraná – Brazil. We provide a conceptualization of the term ritual-festival and a historical overview from its origins to the current format, blending the concepts of sacred and profane by Eliade (1992). Considering the event as a ritual-festival, it was necessary to identify semiology elements – real effects, hypotyposis, useless details and Esto – that demonstrate the dramatic elements present in it and differentiate it from other similar events. To do so, we selected Barthes (1964; 1988; 2004; 2007) and Kowzan's (2006) semiology as the main analytical approaches regarding Theatre Semiology. Additionally, we considered Pavis (2000; 2015) and Fernandes' (2013) concepts of theatricality in order to analyze interactions in the event within this perspective. With the support of the analysis of the documentary "Teatralidade em Ivana Kupala – Mallet, 09 de julho de 2022", in which the interactions with the fortune teller Mama Solotka are featured, we conducted an analysis of the character's presence on stage, highlighting the presented theories listed for this purpose and identifying theatricality in the actress' performance.